The Enemy Within? Anti‐Rights Groups and Restrictions on Civil Society. (31st July 2021) - Pousadela, Ines M.; Perera, Dominic R.
Abstract: A growing body of literature focuses on restrictions imposed on the space for civil society, or civic space. Recent research has noted that over the past decade, states have expanded their repertoire of legal and extra‐legal measures to curtail the freedoms of association, expression and assembly. Although time‐series data show that the state apparatus continues to be the primary perpetrator of restrictions on civil society organisations (CSOs) and activists, increasing evidence suggests that non‐state actors (NSAs) also play a relevant role in restricting civic space. A broad and heterogeneous category, NSAs include paramilitary forces, private corporate security, criminal gangs and religious fundamentalist groups, among others. This article analyses civic space restrictions driven by a specific type of NSA, that of so‐called 'anti‐rights groups'. Research conclusions suggest that this distinct set of actors, which usually cultivates close links to the state, is increasingly playing an understudied role in restricting human rights CSOs. Abstract : Anti‐rights groups are an important, yet understudied driver of civic space restrictions.